2012
DOI: 10.1007/s11064-012-0709-1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation Stress During the Prepubertal Period in Rats Induces Long-Lasting Neurochemical Changes in the Prefrontal Cortex

Abstract: Social isolation during postnatal development leads to behavioral and neurochemical changes, and a particular susceptibility of the prefrontal cortex to interventions during this period has been suggested. In addition, some studies showed that consumption of a palatable diet reduces some of the stress effects. Therefore, our aim is to investigate the effect of isolation stress in early life on some parameters of oxidative stress and energy metabolism (Na(+),K(+)-ATPase activity, respiratory chain enzymes activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
11
0
1
Order By: Relevance
“…; Krolow et al . ; Kuchukashvili et al . ); so far, few studies have investigated this effect in acute stress conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Krolow et al . ; Kuchukashvili et al . ); so far, few studies have investigated this effect in acute stress conditions.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that exposure to chronic stress situations induces activation in juvenile (Krolow et al . ) or inhibition of respiratory chain complex in adult (Rezin et al . ).…”
mentioning
confidence: 99%
“…It is important to note that this sensitive period of development requires higher energy, since the brain is in a constant process of organizing and of neural maturation. This is true especially for the prefrontal cortex, which has a characteristic late maturation and is sensitive to external factors such as diet and stress (Krolow et al, 2012; Sherman et al, 2014). The present study showed that the effects of stress alone were different in some responses when associated with a chronic HFD, indicating that different environmental interventions in high plasticity periods may program distinct outcomes in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in BDNF have been associated with memory impairment induced by high fat diet intake (Cui et al, 2012; Granholm et al, 2008), or exposure to stressors early in life (Oomen et al, 2010; Wang et al, 2011). Also relevant to the development of central nervous system is the activity of Na + ,K + ‐ATPase, an enzyme that maintains the neurochemical gradient essential for neuronal excitability, and which activity is influenced by environmental interventions, like stress in early life (Noschang et al, 2012; Silveira et al, 2011) and palatable diet intake (Krolow et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…IR-induced PPI deficits are associated with specific neurochemical and molecular changes in frontal cortex, including alterations in levels of dopamine (DA), immunologic and mitochondrial markers (Krolow et al 2012) [9], synaptic proteins and receptor levels (Hermes et al 2011) [10], expression of genes related to glutamate (Turnock-Jones et al 2009; Murphy et al 2010) [11,12] and GABA function (Murphy et al 2010) [12], and structure, the latter attributed to a loss of mPFC neuropil (Day-Wilson et al 2006) [8]. Such a long list of alterations in the mPFC suggests that the impact of IR on mPFC function is both pervasive and non-selective; it is not yet clear which of these changes – if any - are responsible for reduced PPI, a phenotype associated with neurodevelopmental brain disorders, including schizophrenia (Braff et al 1978; cf.…”
Section: Introductionmentioning
confidence: 99%